Fostering Islamic Character Values through Multimedia Extracurricular Activities: Strategies of Islamic Education Teachers - Diana Safitri; Sugiono; Mona Novita; Akmal Mundiri (Seutia Hukamaa Cendekia, 2025)
This study aims to examine the strategies employed by Islamic Education (PAI) teachers to foster Islamic character values among middle school students through multimedia-based extracurricular activities. Specifically, it investigates how interactive digital tools, reflective exercises, and contextualized learning experiences contribute to the internalization of core values such as honesty, responsibility, empathy, and discipline. Employing a qualitative case study design, data were collected at SMP Hidmatul Hikam Alassumur through direct observations of extracurricular sessions, in-depth interviews with teachers, and document analysis including lesson plans and student portfolios. Findings indicate that multimedia integration significantly enhances student engagement, comprehension, and practical application of Islamic character values, with students demonstrating increased moral awareness and consistent ethical behavior. Teachers’ deliberate planning, continuous feedback, and reflective facilitation were identified as critical success factors. The study highlights the pedagogical potential of technology-enhanced activities in moral education and provides practical guidance for educators seeking to strengthen character development. The results suggest that integrating multimedia thoughtfully into extracurricular programs can foster sustainable moral growth and active value internalization among adolescents.